The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1182/blood-2018-99-110270
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Courses of Orally Administered Fecal Microbiota Transplantation for the Treatment of Steroid Resistant and Steroid Dependent Intestinal Acute Graft Vs. Host Disease: A Pilot Study (NCT 03214289)

Abstract: Background: Steroid-resistant (SR) intestinal acute graft versus host disease (aGVHD) is a devastating complication of allogeneic hematopoietic stem cell transplantation. Preliminary reports suggest that fecal microbiota transplantation (FMT) administered through a nasogastric tube or colonoscopy may be an effective treatment. We report the results of a single-arm pilot study (NCT 03214289) using FMT in capsules to treat SR or steroid dependent (SD) intestinal aGVHD. Methods: The primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Recurrent CDI Webb et al 71 7 No recurrence in 6 Moss et al 72 6 No recurrence in 4 Bluestone et al 73 3 99 1 CR Zhang et all 100 1 CR Zhong et al 101 1 CR Shouval et al 102…”
Section: Therapeuticmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent CDI Webb et al 71 7 No recurrence in 6 Moss et al 72 6 No recurrence in 4 Bluestone et al 73 3 99 1 CR Zhang et all 100 1 CR Zhong et al 101 1 CR Shouval et al 102…”
Section: Therapeuticmentioning
confidence: 99%
“…Response to treatment was seen within a median of 14 days (range: 3-28), with a median of two FMT (range: 1-7), and a median of 7 days between treatments (range: 2-60). 46,[98][99][100][101][102][103][104][105][106] Infectious complications occurred in 11 patients. Two had sepsis with bacteria not originating from FMT, 102 and one patient developed diarrhea due to Norovirus that was traced to FMT.…”
Section: Can Fecal Microbiota Transplantation Mitigate Prevailing Acumentioning
confidence: 99%
See 1 more Smart Citation
“…One paper was excluded because the etiology of diarrhea, reported as the reason for FMT, was not clear [ 32 ]. Of the 23 studies assessed, 15 were case reports or retrospective case series [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], seven were prospective cohorts [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], while only one completed randomized controlled trial was found in the literature [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…After FMT, the introduction of new bacteria and an increase in microbial diversity was found in the recipient’s stool, with a strong reduction in the rate of bacterial dominance. Only two patients achieved complete remission, and one a partial response [ 50 ]. In the case report by Mao et al, after two cycles of oral FMT capsules from unrelated donor, intestinal aGvHD was gradually controlled and did not recur during the two-month follow-up.…”
Section: Resultsmentioning
confidence: 99%